2020
DOI: 10.3892/mco.2020.2025
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and maternal and foetal management of pregnancy‑complicating Krukenberg tumours

Abstract: Krukenberg tumours are not uncommon, but pregnancy-complicating Krukenberg tumours are rare. To identify management strategies of pregnancies with Krukenberg tumours, the medical records of patients treated at Peking Union Medical College Hospital over the past 20 years were collected and analysed. Four patients were enrolled. The primary tumour sites were the stomach and colorectal region. Three patients presented with obvious and severe gastrointestinal symptoms at 11-18 weeks of gestation, and their symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Follow-up found that the newborn was alive and the growth and development were normal. The treatment of ovarian malignant tumors requires a comprehensive assessment of the tumor (degree of malignancy), pregnant women and their families (the physical condition of the pregnant women, the expectation of the pregnant women and their family members for the fetus), the fetus (gestational age, survival ability), the hospital's critically ill newborns and critically ill pregnant women's ability and other factors [11,12].…”
Section: Treatmentmentioning
confidence: 99%
“…Follow-up found that the newborn was alive and the growth and development were normal. The treatment of ovarian malignant tumors requires a comprehensive assessment of the tumor (degree of malignancy), pregnant women and their families (the physical condition of the pregnant women, the expectation of the pregnant women and their family members for the fetus), the fetus (gestational age, survival ability), the hospital's critically ill newborns and critically ill pregnant women's ability and other factors [11,12].…”
Section: Treatmentmentioning
confidence: 99%
“…Based on 48 studies from an electronic database of 3,025 women with Krukenberg tumours, Lionetti et al reported that 39.7% of patients were ≥50 years of age (11) . Rare cases of Krukenberg tumours in pregnant women have also been described (12,13) . Bilateral and synchronous Krukenberg tumours account for about 60-80% and over 63% of cases, respectively.…”
Section: Introductionmentioning
confidence: 99%